GIFT —An R package to access the Global Inventory of Floras and Traits - Denelle, Pierre; Weigelt, Patrick; Kreft, Holger (Methods in ecology and evolution, 2023)
Advancing knowledge of biodiversity requires global open‐access databases. Having large‐scale information on plant distributions, functional traits and evolutionary history will enable the scientific community to improve its understanding of the patterns and drivers of plant diversity on a global scale. The Global Inventory of Floras and Traits (GIFT) is a global database of regional plant checklists that has proven successful in documenting biogeographical patterns of plants. Since the release of the first version of GIFT, the database kept on expanding. We introduce GIFT version 3.0, which contains 5169 plant checklists referring to 3400 regions worldwide. These checklists include a total of 371,148 land plant species, mostly vascular plants, of which 354,848 have accepted species names, and species‐level data for 109 functional traits. This new version of GIFT relies on new resources for taxonomic name standardization, is matched to a new plant phylogeny, comes with a new trait aggregation workflow and includes additional environmental variables. We also present the GIFT R ‐package, which contains all necessary functions to retrieve distributional, functional, phylogenetic, and environmental data from the GIFT database. The package comes with a dedicated website, https://biogeomacro.github.io/GIFT/ , which includes three vignettes to guide users in retrieving data from GIFT. The recent development of GIFT and its associated R ‐package provide ecologists with access to one of the largest plant databases. This will foster research into regional to global patterns of plant diversity and their underlying mechanisms. The ability to retrieve and cite data from any previous and current instance of the GIFT database will ensure the reproducibility of studies that utilise it.